2017
DOI: 10.1007/s10887-017-9147-x
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and education: evidence from the cardiovascular revolution

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…In ancillary results,Hansen and Strulik (2017) find no effect of health on income per person aged 30-65 years. Their results are surprising because the salient increase in college education that they document does not manifest in higher incomes, despite the growing college wage premium(Card and Lemieux, 2001).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…In ancillary results,Hansen and Strulik (2017) find no effect of health on income per person aged 30-65 years. Their results are surprising because the salient increase in college education that they document does not manifest in higher incomes, despite the growing college wage premium(Card and Lemieux, 2001).…”
mentioning
confidence: 81%
“…This paper contributes to the literature in several ways. It most closely relates to work by Hansen and Strulik (2017), who are the first to use variation from the cardiovascular revolution to show a causal link between health and college enrollment in the United States. In contrast to their work, I analyze how health dynamics shape life-cycle incomes and which factors explain this process.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The links between life expectancy and education are well documented in literature both contemporary and non-contemporary literature (Sen, 1999 ; Saito, 2003 ; Hansen & Strulik, 2017 ; Olshansky et al, 2012 ; Hendi, 2017 ). According to Sen ( 1999 ), quality education is fundamental to maintaining a healthy lifestyle and well-being.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, few studies have demonstrated that an increase in life expectancy has no adverse effects on economic growth subject to initial health (Hansen, 2014;Hansen & Lønstrup, 2015). Moreover, a negative causal relationship was observed between cardiovascular disease and economic growth in high-income countries, the Organization of Economic Co-operation and Development (OECD) countries and European countries (Hansen & Strulik, 2017;Hyclak et al, 2016;Suhrcke & Urban, 2010). No study is yet conducted to study the impact of health on economic growth in Asian countries.…”
Section: Health and Economic Growthmentioning
confidence: 99%